The Impact of Remote Work on Team Dynamics and Management Strategies - Baker, Abeer Wadullah; Salman, Riyadh Yousuf; Zaur, Elnur Sardarov; Fahmi, Ahmed Mohammed (Journal of Ecohumanism, 2024)
Background: The global pandemic has expedited the transition to remote work, profoundly changing team dynamics and management practices within enterprises. This transition needs an awareness of the implications for communication, cooperation, and leadership. Objective: The aim of this study is to look into the effects of remote work on team dynamics and to determine the management practices that have proven most effective in preserving team cohesiveness and productivity. Methods: A mixed-methods approach was used, with both quantitative surveys and qualitative interviews. Data were obtained from 300 employees from diverse businesses who have done remote work. The survey assessed changes in communication frequency, team cohesion, and perceived productivity, whereas interviews offered more in-depth information about managers’ issues and strategies. Results: The study found a considerable shift in communication patterns, with a rise in asynchronous communication methods. Team cohesion initially deteriorated, but stabilized after virtual team-building exercises were implemented. Regular check-ins, flexible work hours, and the use of collaborative tools to improve contact and project management are among the most effective management tactics observed. Conclusion: Remote work has altered team dynamics, posing both challenges and opportunities for managers. Adaptive management practices can help firms sustain team cohesion and productivity. Future studies should look into long-term effects and the possibility for hybrid work styles to improve team dynamics even further.